Penciptaan Busana Feminine Romantic Style Terinspirasi dari Bunga Celosia Cristata - Annisa Rizki; Desi Trisnawati; Novina Yeni Fatrina; Fadri Rahmat (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
designers in creating clothing that has a strong aesthetic value and character. One of the fashion styles that remains in demand today is the Feminine romantic style. This style displays a soft, graceful impression, through silhouettes, decorative, and soft color choices. The work entitled "Feminine romantic style inspired by the celosia cristata flower" the creation of this clothing has the aim of designing and realizing feminine clothing inspired by the wavy celosia cristata flower. The method of creating this work uses three stages, the first is exploration, namely the process of finding ideas in creating clothing, the second is designing, namely the stage of making sketches and designs, and the third is realization, namely the process of creating works that begin with pattern making, sewing, and ending with finishing. The color selection is a derivative of the pink color of the celosia cristata flower. The materials used are yamaha silk, kawasaki silk, maxmara, tile sugar candy, organza, satin bridal, and Songket Silungkang. The sewing realization process uses ruffle techniques and sequin embroidery techniques. This work is realized in three levels of ready to wear clothing, ready to wear deluxe, and haute couture. This outfit can be worn at fashion shows. It is hoped that this work will inspire innovation in future creations